The importance of children’s outdoor learning in urban areas - Nangkula, Utaberta; Marouf, Noura (Department of Architecture, Faculty of Design and Architecture, Universiti Putra Malaysia, 2013)
In the 21st century, majority of the urban population are extremely young in whole of the world. For instance, youth under the 18 years old has been considered above 48 percent of the population of cities like Delhi and Mexico City; while in manila, Jakarta and Bogota, it reaches to more than 50 percent. Unfortunately, it is the youngsters who are affected the most by the urbanization pressure and hazards (UNICEF and UNDP, 2000). It is predicted that the youth population will be the major category in the worldwide in following years (Boyden, 1991). Regarding to the significant role of playing in children’s lives and development; in order to plan and create more suitable environments for children; Firstly, it is vital to know about the existent situation of children environments and whether their needs meeting in childhood environments or not. Especially in developing countries which, on the basis of statistics, have the largest youth population among the world and the knowledge about children’s environments are limited. And Secondly, it is very important to perform some open-ended qualitative researches to understand the actual needs of children from their eyes (Chawla, 2002b); To address the issues that adults imagine to support children’s environments and spaces design for them; To mention that, it is should start firstly by analyzing and realizing the children’s every day experiences and perceptions of their around environments at the present time. The main objective of this paper is to initiate a discourse on the importance of outdoor learning and outdoor spaces for the development of a children. The discussion will review some issues related with it in a general manners. It is expected from this paper that we can start a deeper research and discourse on the importance to reconstruct and redesign children’s outdoor areas as a part of their learning space.